ANALYSIS OF EXPECTED OUTCOMES OF UZBEKISTAN'S MEMBERSHIP IN THE UNITED NATIONS ECONOMIC AND SOCIAL - Qosimova Nodira Saidovna (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: This study examines Uzbekistan's recent membership in the United Nations Economic and Social Council (ECOSOC) and its anticipated impacts on the nation’s socio-economic development and international standing. The research aims to identify the opportunities and challenges associated with this strategic achievement. Method: The analysis employs a qualitative approach, integrating a review of international policies, socio-economic reform agendas, and comparative case studies of other ECOSOC member states. It evaluates Uzbekistan’s alignment with ECOSOC’s objectives and its potential for leveraging this platform to achieve national and global development goals. Results: The findings indicate that Uzbekistan’s ECOSOC membership offers significant opportunities to strengthen its international presence, advance socio-economic reforms, and access global expertise and resources. Key areas of potential include sustainable development, poverty alleviation, and regional cooperation. Novelty: This research provides a pioneering assessment of the implications of ECOSOC membership for Uzbekistan, offering insights into how emerging economies can capitalize on multilateral platforms for national progress and international integration. The study highlights Uzbekistan’s unique position to bridge regional and global development priorities through its engagement with ECOSOC.